Potential implications of GRP58 expression and susceptibility of cervical cancer to cisplatin and thymoquinone-based therapy - Wan Abd Ghani, Wan Nor Hafiza; Saiful Yazan, Latifah (Dove Medical Press, 2014)
A new therapeutic approach of looking at the expression of glucose-regulated protein (GRP) 58 as an indication of cisplatin sensitivity may eradicate fruitless treatment and side effects in patients with cervical cancer. Thymoquinone, the bioactive compound in Nigella sativa, has been reported to have an antiproliferative effect on cervical cancer cells. This study compared the cytotoxic effects of cisplatin, a drug commonly used in the treatment of cervical cancer, and thymoquinone in cervical cancer (HeLa and SiHa) cell lines by 3-(4,5-Dimethyl thiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and measured GRP58 expression in the cells by quantitative real-time polymerase chain reaction and Western blotting. Cisplatin had higher antiproliferative activity towards the cervical cancer cell lines than thymoquinone in a dose-dependent and time-dependent manner. However, cisplatin was more toxic to normal 3T3 and Vero cell lines than thymoquinone. The half maximal inhibitory concentration (IC50) of cisplatin in HeLa and SiHa cells at 72 hours was 13.3±2.52 μM and 19.5±2.12 μM, respectively. Meanwhile, the IC50 of thymoquinone in HeLa and SiHa cells was 29.57±5.81 μM and 23.41±1.51 μM, respectively (P<0.05). A significant correlation was found between the cytotoxicity of cisplatin and expression of GRP58, but this relationship was not significant for thymoquinone. Therefore, the response of cervical cancer cells to cisplatin can be predicted on the basis of GRP58 expression.